ASSESSMENT OF THE EFFICACY OF DOSE RADIATION THERAPY REGIMENS FOR TREATING CANCER ACCORDING TO CRITERIA FOR EARLY TOXICITY OF RADIOTHERAPY - V. A. Lisin (Сибирский онкологический журнал, 2018)
Optimization of dose fractionation regimens is an important way to increase the effectiveness of radiotherapy for malignant tumors. To choose the optimal radiotherapy regimen, it is necessary to know the nature of tumor regression in different dose fractionation schedules. The purpose of the study was to analyze the patterns of tumor regression in various dose fractionation regimens, while having the same level of normal tissue damage in cases when damage to normal and tumor tissues can be described using the lineal quadratic model. Material and methods. We developed the algorithm for calculating survival of tumor cells under dose fractionation regimes resulting in the same degree of damage to normal tissue. Using this algorithm, the tumor regression patterns were found at various quantitative ratios between the radiosensitivities of the normal and tumor tissues. Results. It was found that in the case of equality of the ratios of radiobiological parameters characterizing the tumor and normal tissues (αt /βt =αn /βn ), the efficacy of radiation therapy did not depend on the dose fractionation regimen at any ratio between the radiosensitivities of the tumor and normal tissues. In the case of , the efficacy of radiation therapy depended on the dose fractionation regimen and increased with decreasing the dose per fraction. On the contrary, in the case of , the efficacy of radiation therapy increased with increasing a single dose. Our theoretical results were consistent with other recent studies.